Mixed mode I + II interlaminar fracture of carbon/epoxy laminates - Pereira, A.B.
This paper reports a study of the mixed mode I + II fracture of carbon/epoxy unidirectional and multidirectional specimens with symmetric, quasi-symmetric and markedly asymmetric legs. A beam model was developed for predicting the compliance and total strain energy release rate, G. Its predictions agreed well with three-dimensional finite element models and with experimental data of double cantilever beam, end-notched flexure and mixed-mode bending tests. The mode mix was determined from a virtual crack closure technique limit value analysis, in order to overcome ambiguity for delaminations between differently oriented plies. Initiation Gc values versus mode II ratio GII/G plots had practically identical shapes, showing a linear Gc increase with GII/G >= 25 %. Multidirectional specimens with quasi-symmetric and markedly asymmetric legs had similar Gc values.